HIV-1 Modulates the tRNA Pool to Improve Translation Efficiency - van Weringh, Anna; Ragonnet-Cronin, Manon; Pranckeviciene, Erinija; Pavon-Eternod, Mariana; Kleiman, Lawrence; Xia, Xuhua (Université d'Ottawa | University of Ottawa, 2011)
Despite its poorly adapted codon usage, HIV-1 replicates and is expressed extremely well in human host cells. HIV-1 has recently been shown to package non-lysyl tRNAs in addition to the tRNALys needed for priming reverse-transcription and integration of the HIV-1 genome. By comparing the codon usage of HIV-1 genes with that of its human host, we found that tRNAs decoding codons which are highly used by HIV-1 but avoided by its host are overrepresented in HIV-1 virions. In particular, tRNAs decoding A-ending codons, required for the expression of HIV's A-rich genome, are highly enriched. Because the affinity of Gag-Pol for all tRNAs is non-specific, HIV packaging is most likely passive and reflects the tRNA pool at the time of viral particle formation. Codon usage of HIV-1 early genes is similar to that of highly expressed host genes, but codon usage of HIV-1 late genes were better adapted to the selectively enriched tRNA pool, suggesting that alterations in the tRNA pool are induced late in viral infection. If HIV-1 genes are adapting to an altered tRNA pool, codon adaptation of HIV-1 may be better than previously thought.
Keywords: HIV-1; tRNA; codon usage; translation efficiency; codon-anticodon adaptation